Analisis Efektivitas Penerapan Strategi Inovasi Berbasis Teknologi E-Commerce pada UMKM Kuliner di Kecamatan Jogoroto - Atmojo, Cahyo; Fahimul Amri (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This study aims to analyze the effectiveness of implementing e-commerce technology-based innovation strategies in culinary MSMEs in Jogoroto District. Using a qualitative descriptive approach, this study identifies the role of digital platforms such as social media, marketplaces, and delivery applications in increasing sales, operational efficiency, and business competitiveness. This study also found that the main obstacles for MSMEs include limited technological knowledge, implementation costs, and lack of innovative marketing strategies. However, the adoption of e-commerce has been proven to be able to expand market reach and significantly increase MSMEs income. The results of the study show that the effectiveness of e-commerce technology is influenced by understanding the program, determining the right target market, and implementing efficient and adaptive marketing strategies. Businesses that successfully use e-commerce are able to strengthen their brands and create real changes in business operations. This study recommends collaboration between the government and MSMEs actors to support digital transformation through technology training and providing access to relevant resources, so that MSMEs digitalization can run sustainably and support the local economy.